ESBL-producing E. coli and K. pneumoniae: prevalence and antimicrobial susceptibility - Giuseppe Miragliotta; Anna Di Taranto; Rossella De Nittis; Raffaele Antonetti; Raffaele Del Prete; Adriana Mosca (Microbiologia Medica, 2009)
Infections caused by extended-spectrum beta-lactamase (ESBL) producing E. coli and K. pneumoniae limit therapeutical options.The objective of this study was to evaluate the activity of ciprofloxacin, imipenem, amikacin and piperacillin/tazobactam against ESBL-producing E. coli and K. pneumoniae strains isolated from patients admitted to Ospedali Riuniti, Foggia, over the period January-December 2007. A total of 1013 E. coli and 146 K. pneumoniae were isolated from various clinical specimens. 111/1013 (10.9%) and 24/146 (16.4%) were confirmed as ESBL-producing strains by both the Phoenix system (Becton & Dickinson) and the E-test (bioMérieux, Italia). Both the ESBL producing enterobacteria showed a high degree resistance to ciprofloxacin; in addition, K. pneumoniae exhibited resistance also to piperacillin/tazobactam. Imipenem was the most effective antibiotic with the exception of one strain ESBL-positive K. pneumoniae. A similar pattern was showed by amikacin. In view of the increasing prevalence of ESBL strains it appears important a continuous antimicrobial monitoring.